Investments in Economic Growth and Structural Transformation of Russia - O. S. Sukharev (Финансы: теория и практика, 2025)
structural transformation, which is understood as a change in the proportions between the basic sectors - processing, raw materials and transaction. In orthodox economic theories, gross fixed capital formation is given a central place in ensuring economic growth in the long term, although in practice there are many conditions that weaken such an impact. The purpose of the study is to identify the modes of the investment process in the coordinates of “investment - risk”, determining the impact on the growth rate and assessing the distribution of investments by economic sectors that form the economic structure. This will allow specifying the tasks of development of the Russian economy, highlighting the directions of structural policy and measures to stimulate economic growth that go beyond the stereotypical orthodox approach, which reduces recommendations to an increase in the accumulation rate and investments. The methodology of the study is the theory of economic growth and structural dynamics, empirical and regression analysis of data, ideas about the investment process and measures to stimulate it, a method for assessing the risk by the standard deviation of gross profit. The result is that the article theoretically identifies several investment dynamics regimes, defining two basic investment types (according to the dynamics of investment and risk) - “risky” and “hedge”. The current growth structure in Russia is assessed as based on risky investments, fixing the relationship between the main sectors and their contribution to the overall GDP growth rate. An empirical analysis of economic growth in Russia in the period 2000-2023 confirms that the dynamics of investments determined the growth rate, which in turn depended on changes in the risk generated by the institutional conditions of development. The risky type of investment also limited growth, and structurally, investments in fixed capital were mainly directed to transaction activities, then to the raw materials sectors and only then to processing. This circumstance actualizes the task of structural changes, which should be reduced to a change in the investment regime and institutional conditions that encourage capital renewal in the manufacturing sectors.